Pengaruh Jumlah Ulir dan Kecepatan Putaran Terhadap Unjuk Kerja Mesin Pengayak Pasir Tipe Rotary - Ali, Haidir; Qiram, Ikhwanul; Rubiono, Gatut (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2019)
In this study conducted a test of rotary sand-type machine with a variation of the angle of 50 and then the number of threads and rotation speed of the sieve. Variations of the number of threads 3, 6 and 9. The test also uses a variety of filter rotation speeds with varying speeds of 30, 40, and 50 rpm. The aim of the study was to gain the impact of the thread count and speed of rotation on the performance of rotary-type sand sieve machines. Based on this study, the effect of thread count and rotation speed of rotary-type sand screening machine work. Obtained the best sieve results found in the number of threads 3 with the highest fine sand obtained weighing 1.25 kg, the high sand yield of 2.18 kg, and the yield of crude sand 2.62 kg. The effect of rotation speed (RPM), obtained by the result of the sieve process with the efficiency of long-time best filter, resulted in 14.44 sec in angle variable 50 and RPM 30.